Determination of the horizontal component of the earth's magnetic field - Christensen, George Luther (My University, 1894)
Introduction: The experiment of which the following is an account, was not undertaken in the hope of discovering new facts or new laws with which physicists were not already fully acquainted, nor can it be said that it had for its object the testing or introduction of any new methods or apparatus of any kind. Its main object was one of personal interest and benefit; and the only excuse for the following pages, will be found in the fact that this end has been so pleasantly realized, and in the hope that a record of the experiment and the results reached, including a description of the apparatus used and an account of the difficulties encountered, may not be without some interest to students at the College who in after years may undertake a similar experiment. “The absolute system of units, introduced by Gauss and Heber”, says Prof. Andrew Gray, “has changed experimental electricity and magnetism into sciences of which the very essence is the most delicate and exact measurements, and enables their results to be expressed in units which are all together independent of the instruments the surroundings, and the locality of the investigator.” More attention is constantly being given to the expression of electric and magnetic forces in absolute measure because of its importance as a basis for the practical units, and perhaps, also, because of the interest such experiments draw forth an account of the great accuracy of results that may be attained with proper precautions.
Citation: Christensen, George Luther. Determination of the horizontal component of the earth's magnetic field. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Earth; Magnetic field; Magnetism; Electricity; Geology; Theses; Manuscripts (documents)